10-year trajectories of depressive symptoms and risk of dementia: a population-based study. (July 2016) - Mirza, Saira Saeed; Wolters, Frank J; Swanson, Sonja A; Koudstaal, Peter J; Hofman, Albert; Tiemeier, Henning; Ikram, M Arfan
Summary: Background: Late-life depressive symptoms have been extensively studied for their relationship with incident dementia, but have been typically assessed at a single timepoint. Such an approach neglects the course of depression, which, given its remitting and relapsing nature, might provide further insights into the complex association of depression with dementia. We therefore repeatedly measured depressive symptoms in a population of adults over a decade to study the subsequent risk of dementia. Methods: Our study was embedded in the Rotterdam Study, a population-based study of adults aged 55 years or older in Rotterdam (Netherlands), ongoing since 1990. The cohort is monitored continuously for major events by data linkage between the study database and general practitioners. We examined a cohort of participants who were free from dementia, but had data for depressive symptoms from at least one examination round in 1993–95, 1997–99, or 2002–04. We assessed depressive symptoms with the validated Dutch version of the Center for Epidemiology Depression Scale (CES-D) and the Hospital Anxiety and Depression Scale-Depression. We used these data to identify 11-year trajectories of depressive symptoms by latent class trajectory modelling. We screened participants for dementia at each examination round and followed up participants for 10 years for incident dementia by latent trajectory from the third examination round to 2014. We calculated hazard ratios (HR) for dementia by assigned trajectory using two Cox proportional hazards models (model 1 adjusted for age and sex only, and model 2 adjusted additionally for APOE ɛ4 carrier status, educational level, body-mass index, smoking, alcohol consumption, cognitive score, use of antidepressants, and prevalent disease status at baseline). We repeated the analyses censoring for incident stroke, restricting to Alzheimer's disease as an outcome, and accounting for mortality as a competing risk for dementia. Findings: From 1993–2004, we obtained data for depressive symptoms from at least one examination round for 3325 participants (median age: 74·88 years [IQR 70·62–80·06], 1995 [60%] women). We identified five trajectories of depressive symptoms in these 3325 individuals, characterised by maintained low CES-D scores (low; 2441 [73%]); moderately high starting scores but then remitting (decreasing; 369 [11%]); low starting scores, increasing, then remitting (remitting; 170 [5%]); low starting scores that steadily increased (increasing; 255 [8%]); and maintained high scores (high; 90 [3%]). During 26 330 person-years, 434 participants developed incident dementia. Only the trajectory with increasing depressive symptoms was associated with a higher risk of dementia compared with the low depressive symptom trajectory, using model 2 (HR 1·42, 95% CI 1·05–1·94; p=0·024). Additionally, only the increasing trajectory was associated with a higher risk of dementia compared with the low trajectory after censoring for incident stroke (1·58, 1·15–2·16; p=0·0041), restricting to Alzheimer's disease as an outcome (1·44, 1·03–2·02; p=0·034), and accounting for mortality as a competing risk (1·45, 1·06–1·97; p=0·019). Interpretation: Risk of dementia differed with different courses of depression, which could not be captured by a single assessment of depressive symptoms. The higher risk of dementia only in the increasing trajectory suggests depression might be a prodrome of dementia. Funding: Erasmus Medical Center; ZonMw; the Netherlands Ministry of Education Culture and Science; and the Netherlands Ministry for Health, Welfare and Sports.